I know I have an obvious bug -- well, a calculation error somewhere. Doing a quick fibonacci code sample, only requirements is NOT to use arrays and NOT to do it recursively.

This is what I came up with, and its obviously wrong!

I am sure the "bad guy" is the line result += (...) but what is wrong?Code:int fibonacci(int userinput) { int result = 0; int counter = 0; if (userinput == 0) return result = 0; else if (userinput == 1) return result = 1; else for (counter = userinput; counter > 1; counter--) { result += ((counter - 1) + (counter - 2)); } return (result); }